Meningkatkan Kemampuan Ibadah Amaliyah Melalui Kegiatan Praktik - Nastiti Mufidah; Maya Zahrotul Maulida (MA'ALIM: Jurnal Pendidikan Islam, 2022)
ABSTRACTIt is very important for children to develop prayer skills, because right prayer will make children become pious and wake up from evil deeds. The development of the correct prayer of children has a very big influence on children to adults, if this is not considered then the wrong practice of prayer will always be carried out by children. Apart from problems with prayer practices, researchers also encountered other problems, namely about the practice of ablution and tayammum. Researchers socialize about prayer, ablution and tayammum in several days, namely Monday, Tuesday, and Wednesday. Researchers make the best use of the time to teach children about these three problems. Because the current situation makes researchers and also children have to be able to minimize the time so that children can get maximum lessons. Before doing the amaliyah worship, the researcher tried to interact with the children about understanding, intentions, and prayers. Initially, there were still many children who did not understand it properly and correctly. After the socialization and practices were held for several meetings, the children experienced a lot of changes, which at first could not practice properly and correctly, now thank God they are better than before.